Flexor tendon injuries: a review. (1st July 2013) - Hill, Rebecca; Chan, Sharon
Abstract : Objectives To provide a comprehensive review of flexor tendon injuries in the hand, their management, and subsequent recovery. Methods A review of the current literature surrounding flexor tendon anatomy, injury, surgical repair, and healing was performed. Results This review examines the flexor tendons of the hand and describes their anatomy, different zones of injury, surgical repair, and their regeneration and rehabilitation following injury. Adhesions, produced as part of the normal inflammatory process and their inhibitory effect on tendon function are studied. In order to address the issue of adhesions, numerous studies have examined surgical techniques, rehabilitation protocols, and the use of pharmacological and biosynthetic agents to reduce adhesions and therefore improve patient outcomes. Discussion The different zones of injury influence the likelihood of a good recovery following surgical repair. In particular, the presence of digital tendon sheaths in 'Zone 2' means that the formation of adhesions between tendons and sheath is a frequent complication that restricts the normal functioning of the tendon. Following surgery, an early active mobilization protocol produces good outcomes on the whole.